2023
DOI: 10.1177/10815589221141815
|View full text |Cite
|
Sign up to set email alerts
|

The effects of colchicine on hospitalized COVID-19 patients: A randomized, double-blind, placebo-controlled clinical trial

Abstract: This study was designed to evaluate the effects of colchicine in the improvement of clinical outcomes of hospitalized COVID-19 patients. This prospective, randomized, double-blind, placebo-controlled clinical trial was conducted on adult patients (>18 years) with severe COVID-19. The included patients were randomly (1:1) assigned to the colchicine (2 mg loading dose followed by 0.5 mg twice daily for 7 days) or placebo group. Both groups received remdesivir and interferon beta-1b. The primary outcome of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A total of 23 RCTs (28 249 participants) were eligible for inclusion in our meta-analysis 15–37. The details of the screening process are presented in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 23 RCTs (28 249 participants) were eligible for inclusion in our meta-analysis 15–37. The details of the screening process are presented in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…This preliminary evidence provided the rationale for several studies testing colchicine in patients with COVID-19 (Table 1). Although there is accumulating evidence on the use of colchicine in hospitalized patients with moderate-to-severe COVID-19, 20–26 this treatment strategy has been tested only in a single study in the out-of-hospital setting 27 . In the COLCORONA trial, colchicine was associated with significantly lower rates of the composite outcome of death or hospital admission compared with placebo among out-of-hospital patients with PCR-confirmed COVID-19 27 …”
Section: Rationale For Colchicinementioning
confidence: 99%
“…One more approach of the treatment is using colchicine, an indirect IL-6 inhibitor, which is also applied in the treatment of coronary heart disease ( Bonifácio et al, 2023 ). Colchicine suppresses the recruitment of neutrophils, inhibits cytoskeleton metabolism, and opposes SARS-CoV-2 functionality in human cells ( Kasiri et al, 2023 ). Rodriguez et al suggested IL-8 antagonists to be prospective agents to treat severe coronavirus infection ( Rodriguez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%